An introduction to theory of computation [ - Malone, Sherwood (New York : Learning Press, 2014)
This book provides a comprehensive introduction to Theory of Computation
1.Theory of computation -- 2. Computability theory -- 3. Computational complexity theory -- 4. Automata theory and quantum computer -- 5. Models of computation -- 6. Parallel computing
Keywords: Computable functions; Machine theory